2019
DOI: 10.1039/c9bm00799g
|View full text |Cite
|
Sign up to set email alerts
|

Sulfosalicylic acid/Fe3+ based nanoscale coordination polymers for effective cancer therapy by the Fenton reaction: an inspiration for understanding the role of aspirin in the prevention of cancer

Abstract: A new type of pH-responsive nanoscale coordination polymer for ROS-enhanced cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The criteria of VIP > 1, |log2(FC)| > 2, and P-value < 0.05 were used to compare the differential metabolites in untreated patients with those in healthy people or in IPED-treatment patients. The finding of norethisterone acetate, a synthetic derivative of progestogen commonly used in therapy for contraception and ovulation inhibition, and sulfosalicylic acid, a derivative of salicylic acid that acts as a chelating agent for iron ions [23], suggests that patients with PLC-SDES may have a risk of exposure to drug residues, since neither of these two compounds can be synthesized by the human body.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria of VIP > 1, |log2(FC)| > 2, and P-value < 0.05 were used to compare the differential metabolites in untreated patients with those in healthy people or in IPED-treatment patients. The finding of norethisterone acetate, a synthetic derivative of progestogen commonly used in therapy for contraception and ovulation inhibition, and sulfosalicylic acid, a derivative of salicylic acid that acts as a chelating agent for iron ions [23], suggests that patients with PLC-SDES may have a risk of exposure to drug residues, since neither of these two compounds can be synthesized by the human body.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the iron-catalyzed ROS production pathway (called as Fenton reaction) has been widely accepted. [24][25][26] Using the key role of iron in ferroptosis, various iron-based nanostructures have been developed for ferroptosis-inducing cancer therapy, [27][28][29] such as Fe 3 O 4 , [30][31][32][33][34] g-Fe 2 O 3 , 35 FePt, 36 Fe 3+ /polymer, [37][38][39][40][41] Iron-MOF, 42,43 FeS 2 -PEG 44 and oxide iron-based nanocomposites. [45][46][47] More importantly, Mn(0.25)-Fe 3 O 4 -III NPs act as Fenton agents, which show extremely high Fenton reaction activity compared with numerous reported iron-based nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Previous studies have focused on the physicochemical property of metal unit in coordination polymers, such as magnetic properties for MRI imaging and Fenton activity for chemo-dynamic therapy. [26][27][28][29] However, metal ions detached from the intrinsically biodegradable coordination polymers would also take part in life processes, especially the immune system. [30][31][32] For instance, it has recently been reported that manganese ions and zinc ions could greatly enhance the Cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway, and subsequently triggers multifaceted type I interferon-driven inflammatory responses to activate innate immune.…”
Section: Introductionmentioning
confidence: 99%